The tyrosine phosphatase STEP: implications in schizophrenia and the molecular mechanism underlying antipsychotic medications - Nikisha Carty; Jin Xu; PU Kurup; Jonathan Brouillette; Susan Goebel-Goody; Daniel Austin; P Yuan; G Chen; Paulo Rogério Corrêa; V. Haroutunian; Christopher Pittenger; Paul J. Lombroso (2012)
Glutamatergic signaling through N-methyl-D-aspartate receptors (NMDARs) is required for synaptic plasticity. Disruptions in glutamatergic signaling are proposed to contribute to the behavioral and cognitive deficits observed in schizophrenia (SZ). One possible source of compromised glutamatergic function in SZ is decreased surface expression of GluN2B-containing NMDARs. STEP61 is a brain-enriched protein tyrosine phosphatase that dephosphorylates a regulatory tyrosine on GluN2B, thereby promoting its internalization. Here, we report that STEP61 levels are significantly higher in the postmortem anterior cingulate cortex and dorsolateral prefrontal cortex of SZ patients, as well as in mice treated with the psychotomimetics MK-801 and phencyclidine (PCP). Accumulation of STEP61 after MK-801 treatment is due to a disruption in the ubiquitin proteasome system that normally degrades STEP61. STEP knockout mice are less sensitive to both the locomotor and cognitive effects of acute and chronic administration of PCP, supporting the functional relevance of increased STEP61 levels in SZ. In addition, chronic treatment of mice with both typical and atypical antipsychotic medications results in a protein kinase A-mediated phosphorylation and inactivation of STEP61 and, consequently, increased surface expression of GluN1/GluN2B receptors. Taken together, our findings suggest that STEP61 accumulation may contribute to the pathophysiology of SZ. Moreover, we show a mechanistic link between neuroleptic treatment, STEP61 inactivation and increased surface expression of NMDARs, consistent with the glutamate hypothesis of SZ.